An Efficient Min-Max and ACO Algorithms for Cloud Load Balancing - Dr G.Sridevi, E. Harisha, CH. Anusha, G. Lahari, K.R.N.V. Padmaja (International Journal of Advanced Science and Technology, 2020)
Cloud computing is an evolving field in which customers can manage applications with increased tensile, flexibility and fault tolerance. To minimize framework and maintenance expenses, everyone needs to use the services from the cloud. Thus, cloud load is increasing every day. Load Balancing is one of the key issue faced recently by cloud computing. It has many algorithms that work in different ways and have some merits and demerits. This paper discusses the concepts related to cloud Load Balancing algorithms, services provided by cloud environment and finally explore the performance metrics in terms of virtual machines used and allocation of resources.